Inhibiting KDM6A Demethylase Represses Long Non-Coding RNA Hotairm1 Transcription in MDSC During Sepsis - Bah, Isatou; Youssef, Dima; Yao, Zhi Q.; McCall, Charles E.; El Gazzar, Mohamed (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) prolong sepsis by promoting immunosuppression. We reported that sepsis MDSC development requires long non-coding RNA Hotairm1 interactions with S100A9. Using a mouse model that simulates the immunobiology of sepsis, we find that histone demethylase KDM6A promotes Hotairm1 transcription by demethylating transcription repression H3K27me3 histone mark. We show that chemical targeting of KDM6A by GSK-J4 represses Hotairm1 transcription, which coincides with decreases in transcription activation H3K4me3 histone mark and transcription factor PU.1 binding to the Hotairm1 promoter. We further show that immunosuppressive IL-10 cytokine promotes KDM6A binding at the Hotairm1 promoter. IL-10 knockdown repletes H3K27me3 and reduces Hotairm1 transcription. GSK-J4 treatment also relocalizes nuclear S100A9 protein to the cytosol. To support translation to human sepsis, we demonstrate that inhibiting H3K27me3 demethylation by KDM6A ex vivo in MDSCs from patients with protracted sepsis decreases Hotairm1 transcription. These findings suggest that epigenetic targeting of MDSCs in human sepsis might resolve post-sepsis immunosuppression and improve sepsis survival.